Legality of Khulu' Lawsuit for Wives in the Provisions of Legislation in Indonesia - RR Dewi Anggraeni; Dianna Primadianti; Saptaning Ruju Paminto; Nur Rohim Yunus (Jurnal Ilmiah Al-Syir'ah, 2022)
The solution household crisis provided by the wife and accepted by the husband is known as a khulu' in Islamic law. This study examines the legal protection for a wife if the surrender of khulu' is determined and investigated. As well as the relationship between the provisions and the concept of khulu' with the position of women in marriage law which is sourced from the Compilation of Islamic Law related to Marriage Law.. It was decided to apply the research method of normative juridical research in conjunction with a statutory approach. The findings of this study indicate surrender of khulu' to the husband to divorce himself from the marriage bond is accompanied by the payment of 'iwadh', namely the payment of money or goods to the husband from the wife's side as a reward, divorce as a form of legal protection for the wife. The text states that 'iwadh is a system of legal protection given by the state to the wife who proposes khulu'.